Tensile Bond Strength of Customized Cast Post and Core Cemented with Two Luting Agent - Jane Amelia; Deddy Firman; Lisda Damayanti (SONDE (Sound of Dentistry), 2022)
Introduction. Intraradicular posts are usually used on teeth that have lost a lot of hard tissue. Many in vitro studies on the tensile bond strengths of various cements used to retain post and core have reported conflicting results.Purpose: The purpose of this study was to compare the tensile bond strength of customized cast post and core cemented with glass ionomer or self adhesive resin cement. Methods. Eight extracted human insisivus were endodotically treated. The root preparations were accomplished using reamers (9 mm in depth and 1.375 mm in diameter). Pattern for cast post and core were made using inlay resin pattern, and specimens were cast in chromium-cobalt alloy. Specimens divided into 2 groups. Cast post and core in group 1 (n=4) were cemented using glass ionomer cement and in group 2 (n=4) cemented using self adhesive resin cement. Tensile bond strength were measured in universal testing machine at crosshead speed of 0.5 mm/min. The results (N) were statistically analyzed by ANOVA (?=.05). Results. There is a difference in the strength of the adhesive between glass ionomer cement and self adhesive resin cement in numerical data, although the difference is not statistically significant.The ANOVA indicated that there were no significant differences among the groups tested. Tensile bond strength mean between glass ionomer and self adhesive resin cement were statistically similar. The mean value of group 1 (glass ionomer) adhesion strength is 209,292 N, group 2 (self adhesive resin) is 196,190 N. Conclusion. Customized cast posts and cores cemented with glass ionomer and self adhesive resin cement demonstrated similar mean tensile bond strength. Keywords: Tensile strength, cast post and core, glass ionomer cement, self adhesive resin cement.